2016
DOI: 10.2196/games.5526
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Serious Game for Handling Obstetrical Emergencies

Abstract: BackgroundThe emergence of new technologies in the obstetrical field should lead to the development of learning applications, specifically for obstetrical emergencies. Many childbirth simulations have been recently developed. However, to date none of them have been integrated into a serious game.ObjectiveOur objective was to design a new type of immersive serious game, using virtual glasses to facilitate the learning of pregnancy and childbirth pathologies. We have elaborated a new game engine, placing the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In another study, it was mentioned that the use of these technologies has upgraded the adequacy of medical education and training and raised the level of diagnosis and treatment [24]. Another study reveals that VR-based Advanced Cardiac Life Support training can provide a learning experience similar to face-to-face training [14].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was mentioned that the use of these technologies has upgraded the adequacy of medical education and training and raised the level of diagnosis and treatment [24]. Another study reveals that VR-based Advanced Cardiac Life Support training can provide a learning experience similar to face-to-face training [14].…”
Section: Discussionmentioning
confidence: 99%
“…46 Previous research into VR as a medium for health education primarily focused on surgical simulation and anatomical visualization. [51][52][53][54] Gautier and colleagues designed a game using the Oculus Rift to simulate obstetrical emergencies. 51 Although not yet tested with students, the obstetrical emergencies game was intended to teach common gynecological pathologies through various virtual scenarios.…”
Section: Potential Uses Of Vr Technology In Pharmacy Educationmentioning
confidence: 99%
“…[51][52][53][54] Gautier and colleagues designed a game using the Oculus Rift to simulate obstetrical emergencies. 51 Although not yet tested with students, the obstetrical emergencies game was intended to teach common gynecological pathologies through various virtual scenarios. Moro and colleagues found that in addition to VR and AR being as effective as tablet-based technology (ie, the use of iPads or Android tablets) for teaching anatomy, they also increased student engagement, interactivity, and enjoyment.…”
Section: Potential Uses Of Vr Technology In Pharmacy Educationmentioning
confidence: 99%
“…8 Concurrent with the renewed interest in VR, 9 an increasing number of systems have been presented in the past years. [10][11][12][13] As described by the manufacturers, these new devices provide improved features, such as higher resolution, faster refresh rate, and wider field of view, at dramatically lower costs than early systems. In addition, new HMDs include built-in tracking mechanisms to estimate the position and orientation of the head in real time, which enables perspective correction and allows users to freely move, at least to some extent, as in the real world in a room-size environment.…”
Section: Introductionmentioning
confidence: 99%